Letter from The Rossendale Union of Boot, Shoe and Slipper Operatives, 1917 (1917)
1917 1914-1918 "Letter from The Rossendale Union of Boot, Shoe and Slipper Operatives, 1917" [T0245.jpg], 1917 Letter from The Rossendale Union of Boot, Shoe and Slipper Operatives to the Secretary of the Labour Party, dated 17th September 1917, concerning the treatment of conscientious objectors during the First World War.